Electrochemical Preparation and Delivery of Melanin–Iron Covered Gold Nanoparticles - Grumelli, Doris Elda (2009)
Thiol-capped gold nanoparticles modified with iron-melanin are attractive because they combine magnetic properties and biocompatibility. The biopolymer modified nanoparticles are prepared and delivered following a three step strategy: i) adsorption of thiol-capped metal nanoparticles on graphite, ii) electrochemical deposition of melanin-iron, iii) potential-induced delivery of the modified nanoparticles to the electrolyte.